Forests and Food: Addressing Hunger and Nutrition Across Sustainable Landscapes - Vira, B.; Wildburger, C.; Mansourian, S. (Open Book Publishers, 2015)
As population estimates for 2050 reach over 9 billion, issues of food security and nutrition have been dominating academic and policy debates. A total of 805 million people are undernourished worldwide and malnutrition affects nearly every country on the planet. Despite impressive productivity increases, there is growing evidence that conventional agricultural strategies fall short of eliminating global hunger, as well as having long-term ecological consequences. Forests can play an important role in complementing agricultural production to address the Sustainable Development Goals on zero hunger. Forests and trees can be managed to provide better and more nutritionally-balanced diets, greater control over food inputs – particularly during lean seasons and periods of vulnerability (especially for marginalised groups) – and deliver ecosystem services for crop production. However forests are undergoing a rapid process of degradation, a complex process that governments are struggling to reverse.This volume provides important evidence and insights about the potential of forests to reducing global hunger and malnutrition, exploring the different roles of landscapes, and the governance approaches that are required for the equitable delivery of these benefits. Forests and Food is essential reading for researchers, students, NGOs and government departments responsible for agriculture, forestry, food security and poverty alleviation around the globe.